Vocabulary learning strategies and foreign language acquisition - Pavičić Takač, Višnja (Second language acquisition ;, 2008)
"This much needed book will be an invaluable text for researchers of language learning strategies and of vocabulary acquisition, and for teachers and teacher educators. It will stimulate the reader to reflect at length, not only on learner strategy deployment, but also on the problematical relationship between instruction and acquisition. It is also imminently suitable for undergraduate and postgraduate students of applied linguistics. The elaborate and detailed review of studies in the field makes the book suitable for those new to the field, while, the results of new research, particularly in the second and third studies, will appeal to those with more advanced knowledge and experience in the area". Dr Muiris O'Laoire, Institute of Technology, Tralee, Ireland."